ANALISIS KARAKTERISTIK MANAJEMEN WAKTU BELAJAR PESERTA DIDIK KELAS XI IPS SMA NEGERI 11 PONTIANAK - Sari, Yulinda; Wicaksono, Luhur; Putri, Amallia (Universitas Tanjungpura, 2023)
This study aims to describe the characteristics of student learning time management in class XI IPS SMA Negeri 11 Pontianak using a quantitative approach and the form of research is a survey. The data source was 115 students of class XI IPS at SMA Negeri 11 Pontianak with a data collection tool in the form of a questionnaire. The results showed that the characteristics of students' learning time management in class XI IPS were in the